2017
DOI: 10.1089/tmj.2016.0243
|View full text |Cite
|
Sign up to set email alerts
|

Bedside Critical Care Staff Use of Intensive Care Unit Telemedicine: Comparisons by Intensive Care Unit Complexity

Abstract: ICU telemedicine needs to develop an agreed upon typology for documenting ICU telemedicine utilization and incorporate these measures into models of its effect on clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 28 publications
3
11
0
Order By: Relevance
“…The authors reported no difference in severity-adjusted mortality or LOS post-intervention. However, they did report decreased mortality for the most severely-ill patients after ICU telemedicine implementation, which is consistent with findings from several other studies (41,53,55,56). In another study conducted within the Veterans Affairs Healthcare System using a methodologically rigorous design across seven hospitals with matched controls, authors did not find an association of ICU telemedicine with patient outcomes, but noted that their study cohort had an extremely low ICU mortality rate of 2.9%, making it difficult to detect a statistically significant reduction in mortality (54).…”
Section: Has Icu Telemedicine Lived Up To Its Promise?supporting
confidence: 89%
See 2 more Smart Citations
“…The authors reported no difference in severity-adjusted mortality or LOS post-intervention. However, they did report decreased mortality for the most severely-ill patients after ICU telemedicine implementation, which is consistent with findings from several other studies (41,53,55,56). In another study conducted within the Veterans Affairs Healthcare System using a methodologically rigorous design across seven hospitals with matched controls, authors did not find an association of ICU telemedicine with patient outcomes, but noted that their study cohort had an extremely low ICU mortality rate of 2.9%, making it difficult to detect a statistically significant reduction in mortality (54).…”
Section: Has Icu Telemedicine Lived Up To Its Promise?supporting
confidence: 89%
“…These positive findings were reinforced by a large study in a single academic center published in 2011 (16). Notably, in this study, remote (49,53). The authors reported no difference in severity-adjusted mortality or LOS post-intervention.…”
Section: Has Icu Telemedicine Lived Up To Its Promise?supporting
confidence: 53%
See 1 more Smart Citation
“…Moreover, insurance carriers are realizing the benefits of telehealth and it is being frequently reimbursed. Telemedicine is also being used more and more for emergency care and crisis management [7]. The lack of qualified providers, the high costs and burden of transportation for persons with SCI and their frequent common acute health problems, such as urinary tract infections, pressure sores and respiratory concerns, make teleSCI an ideal way to provide care.…”
Section: Future Recommendations For Telescimentioning
confidence: 99%
“…Telemedicine was used as early as in the 1930s for telephone consultations for passengers on the Queen Mary [3]. Recently, the use of telemedicine has expanded rapidly with services available directly to patient for common concerns, such as upper respiratory and urinary tract infections [4] and through consultation from healthcare facilities for issues such as diabetic retinopathy [5], acute stroke [6] and intensive care unit patient management [7].…”
Section: Introductionmentioning
confidence: 99%